PELUANG DAN TANTANGAN USAHA RESTORAN BERSERTIFIKAT HALAL - Nony Shilviani; Setyo Riyanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Indonesia is a country with the largest Muslim population in the world and this huge Muslim population brings great business potential. The restaurant business with halal certification is one of the businesses with great potential, along with the increasing awareness of Muslims regarding the obligation to consume halal food and beverages. The halal certification process of the restaurant business is regulated through the Law and involves the authority who is given authorization to conduct, control and certify the Halal Product Assurance System. Although there are many business opportunities that can be obtained from the halal restaurant business, there are also challenges faced, including the readiness of resources, the availability of the halal ecosystem, and the complication of the halal certification process.